Design analysis and fabrication of a special attachment for plasma cutting - Lim, Pei Fen (School of Materials Engineering, University Malaysia Perlis, 2010)
This thesis is to improve inconvenient of ladies handbag when sited for meeting, event and function. A handbag table clamp is made to aid ladies while attending occasions. This is a research on the consumers who also act as respondents to provide the user conception therefore a design the table clamp for ladies handbag is made to improve the quality of life. In this project, an effort has been made to search for patents and existing products in the market. Besides that, the preparatory of questionnaire is conducted to get more data and indirectly to update information about the product value in the market. Based on the data gather and various parameters associate with the design of the clamp is to provide better ergonomics combination to fit to the users. Concept generation with limitation from respondents is to satisfy requirements criteria. Concept selection by Pugh selection method accelerates the finalize design to develop. Technical drawing by using CATIA V5R16 is to clarify the dimension and shape of the parts. Boothroyd-Dewhurst method find out the appropriate material and manufacturing process to develop the design concept. By having analysis of finite element, Von Mises Stress and displacement support the functionality of the design. Basic calculations of stress apply to confirm the design capable and reliable. To concerns about fit, form and function, prototype development is created to make sure the design can be perform as expected. The testing of performance proves the functionality of physical developed design. The handbag table clamp is convenient to bring (small in size), cheap (low cost on manufacturing), durable (made of metal), and nice in design therefore it will definitely be the first choice for those who like to bring a bag to their occasion and wish their bag in good 'hand'.